Pengaruh Struktur Modal, Capital Intensity, Dan Ukuran Perusahaan Terhadap Tax Avoidance - Efendi, Muhamad; Winingrum, Sri Putri (Jurnal Ekonomika Dan Bisnis (JEBS), 2025)
This research aims to determine the influence of capital structure, capital intensity and company size on tax avoidance. This research phenomenon on tax avoidance that occurred in 2019 was carried out by PT. Akasha Wira International Tbk (ADES) revealed that the company had carried out tax avoidance to maintain the optimal position of the resulting business profits or it was indeed caused by the company's unhealthy financial condition, however, in its implementation there were many violations that were detrimental to the reputation and state or procedures for implementing avoidance. taxes are carried out in an illegal way, cases of fraud in the tax evasion process were carried out by PT Ades Tbk in 2019, based on the fact that an audit by an independent party PT Ades Tbk provided irrelevant information between the amount of production and the business profits they generated, Apart from that, PT Ades Tbk was also identified as disguising the name of a subsidiary by using affiliates in the name of a company outside Indonesia and providing false information about the existence of the subsidiary. The variables used in this research are capital structure (X1), capital intensity (X2), company size (X3) and tax avoidance (Y). The sample selection method uses purposive sampling. The sample size for this research is 40 companies with a total of 200 data and uses natural logarithms because there are values ​​that are too small. This research uses the Eviews 9 analysis tool. The panel data regression model is used as the methodology for this research. The research results show that the selected model is the Fixed Effect Model. The measurement used for the capital structure variable uses the Debt to Equity Ratio (DER), the capital intensity variable uses the Capital Intensity Ratio (CIR), the company size variable uses (SIZE). The results of this research simultaneously show that capital structure, capital intensity and company size influence tax avoidance. Partial research results show that capital structure has no effect on tax avoidance, capital intensity has no significant effect on tax avoidance, company size has an effect on tax avoidance.